WEB BASED RESERVATION SYSTEM DESIGN AT CAFÉ GARTENHUTTE - Muchamad Ilham Rajab Al Mubarok; Sumarno Sumarno (Journal of Artificial Intelligence and Digital Economy, 2025)
Objective: This study aims to design and develop a web-based reservation system for Café Gartenhütte using the User-Centered Design (UCD) method to enhance customer efficiency, convenience, and overall user experience in the reservation process. Method: The research adopts a user-focused approach through several stages, including collecting user requirements via interviews and surveys, designing an intuitive and responsive interface, and conducting usability testing to evaluate system performance and user satisfaction. Results: The developed web application successfully enables customers to make online reservations, manage booking schedules, and receive automated reservation confirmations. The implementation of this system has improved service speed, reduced manual errors, and enhanced both customer satisfaction and operational productivity at the café. Novelty: The distinct contribution of this research lies in the integration of the UCD approach into the reservation system design for small-scale businesses, ensuring that every development stage is based on real user needs, thereby producing a more efficient, user-friendly, and adaptable digital service platform.